PERBANDINGAN PERTUMBUHAN TANAMAN PORANG (Amorphophallus muelleri) AGROFORESTRY DAN MONOKULTUR PADA KELOMPOK TANI SARI BUNGA KAYU KABUPATEN LUWU TIMUR - Maria Maria; Srida Mitra Ayu; Lani Lani (Universitas Andi Djemma Palopo, 2021)
This study aims to determine the comparison of the growth of porang plants managed by agroforestry and monoculture. This research took place from April to May 2021. The data was collected in the form of primary data and secondary data. This study was a completely randomized design consisting of 2 treatments and eight replications on agroforestry and monoculture land so that there were 32 experimental units. Treatment using media M1=Soil (100%) and M2=Soil + husk charcoal. Furthermore, analysis of variance (Manova) was carried out; the analysis of variance showed that on agroforestry land, the treatment had a very significant effect on stem height and substantially impacted the number of leaves. In contrast, in monoculture, the treatment significantly impacted stem height and had no significant effect on the number of leaves. Based on the results of the research, the best porang plant growth was found on agroforestry land that used soil + husk charcoal in terms of plant height parameters and a number of leaves with an average plant height value of 27.2 cm and gave the best results on the number of leaves with an average value of 3 strands. At the same time, the lowest porang plant growth was on monoculture land with an average plant height value of 19 cm and the number of leaves with an average value of 1 strand.